(untitled) - Singh, Harbhajan (Hoboken, N.J., 2006)
Mycoremediation' provides comprehensive coverage, history, and the most up-to-date account of this dynamic and emerging field. It focuses on the current status of role of fungi in biodegradation and bioremediation of various hazardous wastes and wastewaters.
Keywords: Fungal remediation,Tiêu diệt nấm mốc